Rapid neonatal hearing screening using modified automated auditory brainstem response maximum length sequences - Dzulkarnain, Ahmad Aidil Arafat; Wilson, Wayne; Bradley, Andrew; Petoe, Matthew (2005)
As the number of Universal Newborn Hearing Screening (UNHS) programmes increases both in Australia and around the world, so does the need to reduce the time required to screen each child. This paper will describe the results of a new form of auditory brainstem response screening that will combine the previous technologies of maximum length sequence (MLS) stimulus-recording - to reduce the time required to acquire the ABR signal - and automated signal detection - to reduce the time required to analyse the ABR signal. ABR signals will be acquired from approximately 50 newborns who will be assessed using both the standard ABR at stimulus rates of 33 and 66 clicks/s, and an MLS ABR at stimulus rates of 66, 133 and 266 clicks/s, all at a stimulus level of 35dBnHL, using a researcher constructed evoked potentials system. The time required to complete the ABR screening will then be compared offline for all combinations of stimulus, recording and automated analysis paradigms, with the automated analyses to include wave V amplitude, template matching, peak-trough detection, cross-correlation, and signal-to-noise ratio. Should this investigation be successful, further development of the new ABR system could lead to significant reductions in the time and cost of UNHS both in Australia and internationally.